2015
DOI: 10.4238/2015.december.16.20
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EsMcsu1 from the halophytic plant Eutrema salsugineum promotes abscisic acid biosynthesis and increases drought resistance in alfalfa (Medicago sativa L.)

Abstract: ABSTRACT. The stress phytohormone abscisic acid (ABA) plays pivotal roles in plants' adaptive responses to adverse environments. Molybdenum cofactor sulfurases influence aldehyde oxidase activity and ABA biosynthesis. In this study, we isolated a novel EsMcsu1 gene encoding a molybdenum cofactor sulfurase from Eutrema salsugineum. EsMcus1 transcriptional patterns varied between organs, and its expression was significantly upregulated by abiotic stress or ABA treatment. Alfalfa plants that overexpressed EsMcsu1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The accumulation of proline and increased activity of antioxidants, such as SOD, APX (Ascorbate peroxidase), and CAT (Catalase), are known to play important roles in the induction of salt tolerance (Abraham and Dhar, 2010;Fan et al, 2012). Our data showed that proline levels increased during salt stress, especially in transgenic plants ( Figure 4A), which is consistent with findings in transgenic plants overexpressing EsMcsu1 from Eutrema salsugineum (Zhou et al, 2015). SOD activity declined after NaCl treatment, but to a lesser extent in transgenic plants than in WT plants ( Figure 4B).…”
Section: Discussionsupporting
confidence: 81%
“…The accumulation of proline and increased activity of antioxidants, such as SOD, APX (Ascorbate peroxidase), and CAT (Catalase), are known to play important roles in the induction of salt tolerance (Abraham and Dhar, 2010;Fan et al, 2012). Our data showed that proline levels increased during salt stress, especially in transgenic plants ( Figure 4A), which is consistent with findings in transgenic plants overexpressing EsMcsu1 from Eutrema salsugineum (Zhou et al, 2015). SOD activity declined after NaCl treatment, but to a lesser extent in transgenic plants than in WT plants ( Figure 4B).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, PAs can directly bind several macromolecules, including proteins and nucleic acids, and protects them against ROS-induced oxidative injuries. Our data showed that the values of IL and MDA, which are important indexes of membrane damage [ 29 , 30 ], were much lower in the inoculated plants than in the control plants under DS conditions. Similarly, the inoculated plants had lower ROS production and MDA and IL levels than the control plants under PEG-induced stress conditions (mimic drought stress).…”
Section: Discussionmentioning
confidence: 86%
“…The scavenging capacity for reactive oxygen species (ROS) is essential for plants to tolerate drought stress [ 29 , 30 ]. Two major types of ROS including O 2 − and H 2 O 2 were detected in both the control and inoculated plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Georg-Kraemer et al (2011) analyzed differential gene expression patterns in Hordeum euclaston. Zhou et al (2015) isolated a novel EsMcsu1 gene encoding a molybdenum cofactor from Eutrema salsugineum, which promotes the ABA biosynthesis and increases drought resistance in alfalfa. However, there is still little information about the SnRK2, PYR/PYL/RCAR, and ABF gene families in Tibetan hulless barley (Hordeum vulgare L. var.…”
Section: Introductionmentioning
confidence: 99%